2018
DOI: 10.3390/molecules23020469
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Phenylpropanoid Biosynthetic Genes and Their Accumulation in Bitter Melon (Momordica charantia)

Abstract: Phenylpropanoids and flavonoids belong to a large group of secondary metabolites, and are considered to have antioxidant activity, which protects the cells against biotic and abiotic stresses. However, the accumulation of phenylpropanoids and flavonoids in bitter melon has rarely been studied. Here, we identify ten putative phenylpropanoid and flavonoid biosynthetic genes in bitter melon. Most genes were highly expressed in leaves and/or flowers. HPLC analysis showed that rutin and epicatechin were the most ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The reason is that high blue light in LED-mix greatly contributes to the increase of the secondary metabolites such as phenols and flavonoids as compared with other treatments [26, 82, 83]. More studies suggested that blue light should be recommended as a supplementary light source for accumulation of phenols and flavonoids [84, 85]. Moreover, the promotion of primary metabolism partly promoted contents of phenols and flavonoids in the LED-mix treatment (Table 3), since the products of primary metabolism are utilized to synthesize a wide range of secondary metabolites through the shikimate pathway, mevalonic acid pathway, and methylerythritol 4-phosphate (MEP) pathway in higher plants [8689].…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that high blue light in LED-mix greatly contributes to the increase of the secondary metabolites such as phenols and flavonoids as compared with other treatments [26, 82, 83]. More studies suggested that blue light should be recommended as a supplementary light source for accumulation of phenols and flavonoids [84, 85]. Moreover, the promotion of primary metabolism partly promoted contents of phenols and flavonoids in the LED-mix treatment (Table 3), since the products of primary metabolism are utilized to synthesize a wide range of secondary metabolites through the shikimate pathway, mevalonic acid pathway, and methylerythritol 4-phosphate (MEP) pathway in higher plants [8689].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a previously published compound extraction method was used [26] with some modifications. Phenylpropanoids were extracted by adding 2 mL MeOH (80%) to each sample (100 mg), vortexing and incubating for 1 h in a sonicator (Branson Ultrasonic Co., Danbury, CT, USA), then centrifuging (12,000 rpm at 4 • C) for 15 min.…”
Section: Analysis Of Phenylpropanoid Content By Hplcmentioning
confidence: 99%
“…Samples of wheat sprouts were extracted and subjected to HPLC analysis of soluble phenolic compounds using the method by Cuong et al, (2018) with slight modifications [27]. Prior to HPLC analysis, samples of wheat sprouting were freeze-dried at −80 • C for at least 48 h, and then ground into a fine powder using mortar and pestle.…”
Section: Analysis Of Phenylpropanoid Content By Hplcmentioning
confidence: 99%
“…After centrifugation at 10,000 g for 15 min, the supernatants were filtered through 0.45-µm filters for HPLC analysis. The conditions and gradient program for HPLC, used in this study, have previously been described by Cuong et al, (2018) [27]. HPLC analysis was performed with a C18 column (250 mm × 4.6 mm, 5 µm; RStech; Daejeon, Korea).…”
Section: Analysis Of Phenylpropanoid Content By Hplcmentioning
confidence: 99%